MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KARAKTER WASAKA MUATAN IPAS MENGGUNAKAN MODEL PBL, NHT DAN TGT TERINTEGRASI STEAM PADA SISWA SEKOLAH DASAR - Putri Nugroho, Ade; Annisa, Muhsinah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this research is the low level of critical thinking skills and WASAKA character. The solution to the problem in this research is by using the Problem Based Learning, Number Heads Together, and Teams Game Tournament models integrated with STEAM. The purpose of this research is to analyze critical thinking skills and WASAKA character. The research used is classroom action research, with two cycles, namely Cycle I and Cycle II, involving 20 fourth-grade students of SD. The results of this study show that students’ critical thinking skills reached 100% with the very critical criteria. The WASAKA character of students reached 100% with the internalized criteria.